Analisis Pengendalian Kualitas Produk Dengan Menggunakan Metode Seven Tools Dan Kaizen Untuk Mengurangi Kecacatan Produk.: (Di CV. Solusi Offset Yogyakarta ) - Dos Santos, Gregorio; Mawadati, Argaditia; Susetyo, Joko (Jurnal Rekavasi, 2022)
This research discusses about quality control of book production at CV. Solusi Offset to achieve, maintain, and improve product quality. The purpose of this research is to propose one of the quality control methods in book production at CV Solusi Offset using the seven tools and kaizen methods. The seven tools method is used to identify problems and factors that cause defects in order to find solutions for improving the quality of book products at CV Solusi Offset, while kaizen offers suggestions for improvements to these problems. The results of the check sheet show that in 20 months during the period April 2021-September 2022 that the calculation of the average proportion of defects reached 5.9%, while the company's determination of the proportion of defects is 2-3%. Based on the results of data processing and analysis of the results that have been carried out, it can be concluded that the types of defects occur in cover printing, lamination, imprecise book backs, and inverted book filling. Overall, the causes of defects are caused by irregular maintenance, poor preparation of operation strategies, human error, and environmental factors. To overcome these problems, the author proposes the application of the kaizen method (seiri, seiton, seiketsu, seiso, and shitsuke) which adopts five steps for continuous improvement of processes and products with the responsibility of all workers.